(untitled) (Sinología hispánica. China Studies Review, 2016)
Argumentativeness is an attribute not to be neglected in the crisis communication discourse. This paper constructs an argumentation-oriented public crisis communication model. The new model incorporates the well-established rules and two-way symmetric principle in crisis communication with argumentation analysis and evaluation under the theory of pragmadialectics. By analyzing the strategies and evaluating the effects of a local Chinese government’s crisis communication related with a proposed NIMBY facility in Mainland China, the case is employed to underline the significance of the new model in real crisis communication.